n-3 polyunsaturated fatty acids suppress the localization and activation of signaling proteins at the immunological synapse in murine CD4(+) T cells by affecting lipid raft formation - Kim, Wooki (2008)
The molecular properties of immunosuppressive n-3 polyunsaturated fatty acids (PUFA) have not been fully elucidated. Using CD4(+) T cells from wild type control and fat-1 transgenic mice (enriched in n-3 PUFA), we show that membrane raft accumulation assessed by Laurdan (6-dodecanoyl-2-dimethyl aminonaphthalene) labeling was enhanced in fat-1 cells following immunological synapse (IS) formation by CD3-specific Ab expressing hybridoma cells. However, the localization of PKCθ, PLCγ-1 and F-actin into the IS was suppressed. In addition, both the phosphorylation status of PLCγ-1 at the IS and cell proliferation as assessed by CFSE labeling and [(3)H]-thymidine incorporation were suppressed in fat-1 cells. These data imply that lipid rafts may be targets for the development of dietary agents for the treatment of autoimmune and chronic inflammatory diseases.